How do banks screen innovative firms? Evidence from start-up panel data - Martin Brown; Hans Degryse; Daniel Höwer; María Fabiana Penas (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2012)
Start-up firms often face difficulties in raising external funds. Employing a unique panel dataset covering 9,715 start-up firms over the period 2007-2009, we find that high-tech startups are less likely to use bank finance and face more difficulties in raising bank finance than low-tech start-ups. We find that external credit scores do affect the availability of credit for start-up firms, but that banks rely less on external rating information in their decision making for high-tech start-ups than low-tech start-ups. Start-ups that have their main relation with a small bank use more bank finance and report less difficulties in getting credit. By contrast, a greater expertise of the bank in the firm's industry is not associated with fewer difficulties to get bank loans. There are no differences between high-tech and low-tech start-ups regarding the impact of bank size.
Keywords: G2; G18; O16; P34; 330; Innovation; Start-up; Credit information sharing; Soft information; Unternehmensgründung; Innovation; Kredit; Kreditwürdigkeit; Informationsverbreitung; Bank; Deutschland